PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI KAIDAH PENCACAHAN MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN QUIZIZZ - Jayaningtyas, Zulhijjati; Pramasdyahsari, Agnita Siska; Handayani, Evi Suprihatin; Zuhri, Muhammad Saifuddin (EMTEKA: Jurnal Pendidikan Matematika, 2024)
This research were about improving mathematical problem solving abilities through the application of the PBL model assisted by Quizizz to enumeration rule material. This research was motivated by the low ability of students to solve mathematical problems in enumeration rule material, as many as 69.44% of students did not pass the specified KKTP, namely 70. The aim of this research is to describe the process of implementing learning by applying the Problem Based Learning model assisted by Quizizz to enumeration rule material and to describe improvements students' problem solving abilities in enumeration rule material. Based on these problems, Classroom Action Research (PTK) was carried out using a spiral design from Kemmis and Mc. Taggart in two cycles. This research uses test instruments to determine the problem solving abilities obtained by students. The results of the research show that the application of the Problem Based Learning model assisted by Quizizz has a positive effect on students' problem solving abilities in enumeration rule material. The results of data analysis concluded that there was an increase in the percentage value of classical learning completeness in cycle I by 57%, while the percentage value of classical learning completeness in cycle II was 87%.